THE INFLUENCE OF PUBLIC RELATIONS CAMPAIGN #NOSTRAWMOVEMENT ON FAST FOOD RESTOURANT CONSUMER PARTICIPATION - Siti Meisyaroh; Marcella Novena (Jurnal Komunikasi dan Bisnis, 2020)
News about environmental issues have led many companies and fast food restaurants like KFC started the Public Relations campaign movement with the theme #NOSTRAWMOVEMENT which was done simultaneously in all of their outlets in Indonesia. KFC Raden Inten becomes case in study. This study aims to determine the influence of the Public Relations campaign #NOSTRAWMOVEMENT will influence consumer participation in KFC Raden Inten. This research uses stimulus- respons (S-R) theory and participation concept which can be interpreted as taking part or taking a role in activities or activities. The author uses this theory because I want to know how much consumer participation is influenced by Public Relations campaign #NOSTRAWMOVEMENT of KFC. Participation is divided into two categories, direct participation and indirect participation. In this study, researchers used quantitative research with a descriptive and explanatory approach. Data collection techniques used in this study were documentation and questionnaire filling as part of the survey. Researchers used a survei method using a questionnaire. Data analysis techniques using validity test, reliability test, normality test, t test, F test and R2 test. Based on the data processing carried out, this study obtained the result that the relationship between the Public Relations campaign variables and consumer participation had a positive and significant influence. Keywords: Public Relations Campaign, Consumer Participation, Consumer Attitude